ANALISIS PENGARUH PERSEBARAN INDUSTRI TERHADAP KERAPATAN VEGETASI DI KOTA CIMAHI - Fahmi Reyhan Ramadhani; Riko Arrasyid; Miptah Sa’id Fauzi; Muhammad Fauzi Ali; Reynaldi Akbar Setiawan (Jurnal Samudra Geografi, 2022)
Cimahi City is the one of cities in west java with an area of 40.2 km. as the administration region, cimahi city become a center of various activities, such on trade sector, mainly industrial sector. Besides, cimahi city has agriculture and tourism sector according to the law no. 26 of 2007, green open spaces in urban areas has a proportion of at least 30% of the urban area. With remote sensing terchnology on currently, helping detect land cover distribution in form of vegetation in Cimahi City, detect vegetation distribution pattern, vegetation density and vegetation area on certain area in Cimahi City. This study aims to know distribution pattern, density level of vegetation, and distribution of vegetation using NDVI Technique, and also to know analysis result from using NDVI technique on vegetation density and distribution in Cimahi City. This study data acquired technique from landsat 8 data in 2019 data and landsat 7 data in 2008 and acquiring sampling data. Based on this analysis result, distribution pattern and vegetation density in Cimahi City scattered on 5 class, 1) no vegetation class, 2) very low vegetation density class, 3) low vegetation density class, 4) moderate vegetation density class, 5) high vegetation density class. Most of the area of cimahi city no longer has any green land spread over area based on analysis result from NDVI technique. This is comaparable with distribution industry building in cimahi city.